The first large population based twin study of coeliac disease. Issue 5 (1st May 2002) - Greco, L; Romino, R; Coto, I; Di Cosmo, N; Percopo, S; Maglio, M; Paparo, F; Gasperi, V; Limongelli, M G; Cotichini, R; D'Agate, C; Tinto, N; et al.
Abstract : Background and aims: The genetic load in coeliac disease has hitherto been inferred from case series or anecdotally referred twin pairs. We have evaluated the genetic component in coeliac disease by estimating the concordance rate for the disease among twin pairs in a large population based study. Methods: The Italian Twin Registry was matched with the membership lists of a patient support group. Forty seven twin pairs were recruited and screened for antiendomysial (EMA) and antihuman-tissue transglutaminase (anti-tTG) antibodies; zygosity was verified by DNA fingerprinting and twins were typed for HLA class II DRB1 and DQB1 molecules. Results: Concordance rates for coeliac disease differ significantly between monozygotic (MZ) (0.86 probandwise and 0.75 pairwise) and dizygotic (DZ) (0.20 probandwise and 0.11 pairwise) twins. This is the highest concordance so far reported for a multifactorial disease. A logistic regression model, adjusted for age, sex, number of shared HLA haplotypes, and zygosity, showed that genotypes DQA1*0501/DQB1*0201 and DQA1*0301/DQB1*0302 (encoding for heterodimers DQ2 and DQ8, respectively) conferred to the non-index twin a risk of contracting the disease of 3.3 and 1.4, respectively. The risk of being concordant for coeliac disease estimated for the non-index twin of MZ pairs was 17 (95% confidence interval 2.1–134), independent of the DQ at risk genotype. Conclusion: This study provides substantial evidence for a very strong genetic component in coeliac disease, which is only partially due to the HLA region.